'Keep Your Friends Close': The Role of Informality in the Management of Unequal-sized Collaboration for NZ SMEs. Issue 1 (2nd January 2021) - Yata, Siddharth; Hurd, Fiona
ABSTRACT: Due to knowledge and resource constraints, collaboration is often part of the SME internationalization process. Often, these collaborations involve a larger partner organization. Perceptions of the SME in collaboration are understudied, particularly in relation to unequal size. This research presents case studies of three New Zealand SMEs who engage in international collaboration with larger partners. Although there are benefits gained in collaborating with larger firms, SMEs face challenges managing these partnerships. However, it the strategic use of informal relationships helped to overcome the challenges of size difference. These aspects of informal relationship management represent a theoretical contribution.